Advanced ROCOF protection of distribution systems - Liu, Bohan (2012)
When islanding occurs, power supply from the main grid is interrupted which causes a problem when distributed generators continue to provide power into distributed networks. An islanding situation should be detected accurately soon after the island is formed. Because failure to trip the islanded distributed resource can lead to a number of problems for the resource and the connected load. Although ROCOF islanding detection method is the most commonly employed anti-islanding protection technique, it provides fast detection and easily implementation. It is sensitive to the system disturbance. Therefore, the application of the ROCOF relay to detect system islanding has been limited.